Application of bomb- and Chernobyl-derived radiocaesium for reconstructing changes in erosion rates and sediment fluxes from croplands in areas of European Russia with different levels of Chernobyl fallout. (June 2018) - Golosov, V.N.; Walling, D.E.; Konoplev, A.V.; Ivanov, M.M.; Sharifullin, A.G.
Highlights: The downward diffusion of Chernobyl-derived 137 Cs in soils of European Russia depends on the topographic position. The shape of 137 Cs profiles obtained from valleys bottoms can be used to interpret recent sediment redistribution. The sediment deposits sequestered in sediment sinks can provide valuable information on changing soil erosion rates. A decreasing trend of sedimentation rates between the periods 1963–1986 and 1986–2015 was documented for valley bottoms.